World of Tang Dynasty Poems (WTDPP)/ Lee Shun Fen - Lee Shun , Fen (2003)

(untitled)
World of Tang Dynasty Poems (WTDP) is my final year thesis title. This project documentation is an exercise submitted to the Faculty Computer Science and Information Technology, University of Malaya, as a report for the Final Year Project. WTDP is designed to introduce the Tang Poetry to public and to enhance the understanding ancient of Tang Dynasty. It divided to five modules, there are maintenance module, poems module, poets module, exercises modul and games module. WTDP is display in three languages English, Chinese and Malay. It Consisted many functions such as poem reaction, text recitation. song of poem and so on. This report introduces the WTDP project. In the beginning, the overview, objective, scope, expectation and schedule of project have been defined. The following section was a description on the topic studied and researched during the literature review. In the analysis phase, the Waterfall model with prototyping was selected for the development process. Next, the development tools such as Visual Basic, Microsoft Access, Macromedia Director and so on were chosen. Finally, the system analysis consist the result of analysis on the requirement. Then the design phase is covered the topics of Architecture design, Process design, Database design and Interface design. These topics were shown by many table and figures to describe the design.